Pengembangan Kompetensi Sosial untuk Guru Melalui Pelatihan Berbasis Praktik Reflektif: Penelitian - Layli Nurfadilah; Prasasi Dwi Ramadhani; Salma Dwi Puspita; Novan Ardy Wiyani (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This research employs a qualitative approach using a library research design. Data were collected from accredited journals and analyzed through content analysis to identify themes and patterns related to teachers’ social competence development through reflective practices. This study aims to develop a reflective practice based training model to enhance teachers’ social competence, particularly in primary and Islamic education contexts. Through reflective activities, teachers are expected to strengthen empathy, self-awareness, and collaborative communication within learning environments. This study aims to develop a reflective practice–based training model to enhance teachers’ social competence, particularly in primary and Islamic education contexts. Through reflective activities, teachers are expected to strengthen empathy, self-awareness, and collaborative communication within learning environments.